2011
DOI: 10.1093/her/cyr100
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of the adoption and implementation of a statewide childhood obesity prevention initiative in the New York State WIC Program: the NY Fit WIC process evaluation

Abstract: Process evaluations are critical in determining whether outcome evaluations are warranted. This study assessed the extent to which a childhood obesity prevention initiative, NY Fit WIC, was adopted and implemented by the New York State Supplemental Nutrition Program for Women, Infants and Children (WIC). Process data came from qualitative telephone interviews of 101 WIC local agency directors, following NY Fit WIC trainings. Activities were summarized and cross-tabulated by target level (i.e. participant, staf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 25 publications
1
32
0
Order By: Relevance
“…Notwithstanding the challenges associated with estimating the effects of WIC in multilevel, multisector obesity prevention interventions, the MA‐CORD results contribute to the growing evidence that supports the integration of WIC in high‐risk obesity prevention strategies. The MA‐CORD results are consistent with NY Fit WIC pretest‐posttest comparisons that showed a decrease in the average “amount of time children spend watching TV daily” and an increase in the average “amount of time children spend playing outdoors daily” . To expedite the translation of evidence from MA‐CORD and similar interventions, future outcomes research should incorporate qualitative research methods to assess factors and processes that contribute to effective stakeholder engagement and sustainable cross‐sector partnerships in childhood obesity prevention.…”
supporting
confidence: 80%
“…Notwithstanding the challenges associated with estimating the effects of WIC in multilevel, multisector obesity prevention interventions, the MA‐CORD results contribute to the growing evidence that supports the integration of WIC in high‐risk obesity prevention strategies. The MA‐CORD results are consistent with NY Fit WIC pretest‐posttest comparisons that showed a decrease in the average “amount of time children spend watching TV daily” and an increase in the average “amount of time children spend playing outdoors daily” . To expedite the translation of evidence from MA‐CORD and similar interventions, future outcomes research should incorporate qualitative research methods to assess factors and processes that contribute to effective stakeholder engagement and sustainable cross‐sector partnerships in childhood obesity prevention.…”
supporting
confidence: 80%
“…Studies have shown that breastfeeding initiation increases after WIC peer counselor contact [26], and both breastfeeding initiation and the prevalence of exclusive breastfeeding increased following implementation of the revisions to the WIC food package in California [27,28] and New York [10]. In addition, messages about reducing screen time are vigorously promoted in New York [8,9] and the proportion of WIC participants reporting two or fewer hours of screen time increased slowly but steadily in the years following implementation of the revised WIC program in New York [10].…”
Section: Discussionmentioning
confidence: 99%
“…It further limited children C2 years of age to 1 % or non-fat milk, and required breastfeeding promotion and support including breastfeeding peer counseling [7]. The New York State (NYS) WIC Program has been actively and progressively promoting these and other healthy living activities since 1997 [8,9], and the NYS WIC program was the first in the nation to implement the required USDA food package changes in January 2009. Shortly after implementation of the revised WIC food package, modest changes in food consumption and purchasing patterns among WIC participants in NYS [10], and elsewhere around the country [11][12][13][14][15][16] were observed in cross-sectional studies.…”
Section: Introductionmentioning
confidence: 99%
“…Because data for this study came from WIC-enrolled, low-income children, the observed geographic variation in childhood obesity prevalence trends also raises the possibility that families with WIC-enrolled children are better able to adopt and maintain some healthy lifestyles promoted by the WIC program, such as healthy eating, physical activity, and reduced screen time (20) in some neighborhoods than in others (21). …”
Section: Discussionmentioning
confidence: 99%